?????? ???? ????? ????? ???????? ???????? (????? ????? ???????? ?????? ?????? ?? ????? ???????): Fusha as a Unified Language for all Arabic Speakers (a Sociolinguistic Study of Linguistic Unification in Arab Countries) - Rani Puspita; Ade Nandang (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Abstract: Arabic in its use is divided into a variety of fusha and 'ammiyah. Arabs use fusha as an official language as well as a written language. While the language 'ammiyah is the language used in everyday conversation. Fusha Arabic is an Arabic language whose fushah is maintained and in principle is the same as the Arabic language used during the Jahiliyyah and early Islam. Fusha Arabic is used as the language of education, the language of the mass media, official writings, and in this case Arabic has become the lingua franca that extends throughout the Arab world (Arab World) to this day. The purpose of this research is to find out the role and urgency of fusha Arabic in people's lives in Arab countries. The approach used in this study is a qualitative approach. The research method used is descriptive analytic method. This method was chosen with the aim of describing the object to be studied, namely Fusha Arabic as a unitary language. The data that the writer collected in this study was in the form of qualitative data, namely data in the form of words, schemes and pictures. The conclusions obtained from this study include the diversity of Arabic, be it in terms of language, use, or other matters. Arabic fusha is the unified language for all Arabic speakers and is made the official language of twenty-six Arab countries. Keywords : fusha, unified language, common language, Arab country ?????? ?????: ????? ????? ??????? ?? ????????? ??? ?????? ?????? ?? ?????? ???????. ?????? ??????? ?????? ???? ????? ????? ??? ??????. ????? ??? ??????? ?? ????? ????????? ?? ???????? ???????. ?????? ??????? ?? ??? ????? ??? ?????? ??? ?????? ?? ??? ?????? ??? ??? ????? ??????? ????????? ?? ???????? ?????? ???????. ??????? ??????? ?????? ???? ??????? ???? ????? ??????? ????????? ??????? ? ??? ??? ?????? ????? ????? ??????? ?? ????? ???????? ???? ???? ?? ???? ????? ?????? ?????? (?????? ??????) ??? ????? ???. ????? ?? ??? ????? ?? ????? ??? ?????? ??????? ?????? ?? ???? ????? ?? ????? ???????. ?????? ???????? ?? ??? ??????? ?? ???? ????. ???? ????? ????? ????????? ??? ?????? ?????? ????????. ?? ?????? ??? ??????? ???? ??? ????? ?????? ?????? ??? ??????? ?????? ???? ?????. ???? ???????? ???? ????? ?????? ?? ??? ??????? ??? ??? ?????? ????? ? ??? ?????? ?? ??? ????? ??????? ????. ???? ??????????? ???? ?? ?????? ????? ?? ??? ??????? ???? ????? ??????? ? ???? ?? ??? ????? ?? ????????? ?? ??? ??? ?? ??????. ??????? ?????? ?? ????? ??????? ????? ????????? ?????? ??????? ??? ????? ??????? ??? ?????? ???? ?????. ??????? ????????: ??????? ????? ???????? ????? ????????? ???? ?????